Global benchmarking of children's exposure to television advertising of unhealthy foods and beverages across 22 countries. (11th April 2019) - Kelly, Bridget; Vandevijvere, Stefanie; Ng, SeeHoe; Adams, Jean; Allemandi, Lorena; Bahena‐Espina, Liliana; Barquera, Simon; Boyland, Emma; Calleja, Paul; Carmona‐Garcés, Isabel Cristina; Castronuovo, Luciana; Cauchi, Daniel; et al.
Summary: Restricting children's exposures to marketing of unhealthy foods and beverages is a global obesity prevention priority. Monitoring marketing exposures supports informed policymaking. This study presents a global overview of children's television advertising exposure to healthy and unhealthy products. Twenty‐two countries contributed data, captured between 2008 and 2017. Advertisements were coded for the nature of foods and beverages, using the 2015 World Health Organization (WHO) Europe Nutrient Profile Model (should be permitted/not‐permitted to be advertised). Peak viewing times were defined as the top five hour timeslots for children. On average, there were four times more advertisements for foods/beverages that should not be permitted than for permitted foods/beverages. The frequency of food/beverages advertisements that should not be permitted per hour was higher during peak viewing times compared with other times ( P < 0.001). During peak viewing times, food and beverage advertisements that should not be permitted were higher in countries with industry self‐regulatory programmes for responsible advertising compared with countries with no policies. Globally, children are exposed to a large volume of television advertisements for unhealthy foods and beverages, despite the implementation of food industry programmes. Governments should enact regulation to protect children from television advertising of unhealthy products that undermine their health.